Cultivation of ginseng (Panax ginseng C. A. Meyer) in bioreactor: role of ethylene on cell growth and ginsenosides production - Thanh, Nguyen Trung; Yoeup, Paek Kee (Academia Journal of Biology, 2014)
cell suspension of Panax ginseng was cultivated in bioreactor under different concentrations of ethylene. The synthesis of saponin was greatly reduced in all the ethylene concentrations compared to control. The cell fresh (320 g/L) and dry weight (12.5 g/L) were increased at 10 ppm ethylene concentration at the experiment end. However, at higher ethylene concentration (20 ppm) the fresh and dry weight decreased significantly when compared with control. Ethylene shows a significant effect on sugar metabolism, which reduces the consumption of cations, anions and electrical conductivity (EC), where maximum accumulation of fresh and dry weight was occurred. By comparing with control, special oxygen uptake rate profile was almost unaffected by different concentrations of ethylene indicates that ethylene had no effect on cell respiratory metabolism. These results suggest that ethylene had stimulatory effect on fresh and dry weight production while inhibited saponin content.